Rwanda : Third Review Under the Policy Support Instrument: Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Rwanda. (IMF Staff Country Reports; Country Report ;, 2012)
This paper presents key findings of the Third Review under the Policy Support Instrument (PSI) in Rwanda. Program performance was broadly satisfactory. All end-June quantitative assessment criteria were met. Structural benchmarks were partially met as the pace of implementation of structural benchmarks has slowed somewhat either owing to technical difficulties or capacity bottlenecks. Fiscal consolidation in FY2011/12 and FY2012/13 remains on track and is expected to further anchor macroeconomic stability. The authorities have introduced additional revenue measures for FY2012/13 to preserve the revenue objective of the PSI.